2009
DOI: 10.1097/jnr.0b013e3181b2554b
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Exercise in Obese School-Aged Children

Abstract: Study findings provided information giving a better understanding of exercise perceptions among obese children. Such may be used to assist obese children to increase exercise levels as part of efforts to improve health in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It was stated by Chu (2001) that although gender percentages in obesity rates stayed constant from 1980 to 1994, the trend and prevalence of obesity significantly increased in especially males and females older in age. In the study of Lee et al (2009) which was carried out on 11 students between 11-13 years old selected among 1714 people and composed of 5 open-ended question, it was indicated that information was supplied for obese children to understand the perception of exercises better and that exercises can be beneficial for them as a part for the development of their health. In the study of Allen (2011) performed with 123 7th class students, pre and post-program nutritional food, the importance of physical activity and obesity awareness were evaluated with an educational intervention.…”
Section: Resultsmentioning
confidence: 99%
“…It was stated by Chu (2001) that although gender percentages in obesity rates stayed constant from 1980 to 1994, the trend and prevalence of obesity significantly increased in especially males and females older in age. In the study of Lee et al (2009) which was carried out on 11 students between 11-13 years old selected among 1714 people and composed of 5 open-ended question, it was indicated that information was supplied for obese children to understand the perception of exercises better and that exercises can be beneficial for them as a part for the development of their health. In the study of Allen (2011) performed with 123 7th class students, pre and post-program nutritional food, the importance of physical activity and obesity awareness were evaluated with an educational intervention.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, it is evident that childhood obesity is an epidemic (Lee et al, 2009), one that cannot be solved overnight. Obesity is a multi-factorial problem requiring interventions in the area of dietary habits, physical activity, healthy lifestyle education, and parental involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, childhood and adolescent overweight and obesity have been recognized in the United States (US) as a rapidly increasing, major pediatric health concern (Lee et al, 2009). Nearly one third of children nationwide are overweight (32%) or obese (16%), (Singh & Katz, 2010), and approximately nine million children over six years of age are considered obese (Klish, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations